Efficient Enzymatic Cyclization of Disulfide‐Rich Peptides by Using Peptide Ligases. (25th April 2019) - Schmidt, Marcel; Huang, Yen‐Hua; Texeira de Oliveira, Eduardo F.; Toplak, Ana; Wijma, Hein J.; Janssen, Dick B.; van Maarseveen, Jan H.; Craik, David J.; Nuijens, Timo
Abstract: Disulfide‐rich macrocyclic peptides—cyclotides, for example—represent a promising class of molecules with potential therapeutic use. Despite their potential their efficient synthesis at large scale still represents a major challenge. Here we report new chemoenzymatic strategies using peptide ligase variants—inter alia, omniligase‐1—for the efficient and scalable one‐pot cyclization and folding of the native cyclotides MCoTI‐II, kalata B1 and variants thereof, as well as of the θ‐defensin RTD‐1. The synthesis of the kB1 variant T20K was successfully demonstrated at multi‐gram scale. The existence of several ligation sites for each macrocycle makes this approach highly flexible and facilitates both the larger‐scale manufacture and the engineering of bioactive, grafted cyclotide variants, therefore clearly offering a valuable and powerful extension of the existing toolbox of enzymes for peptide head‐to‐tail cyclization. Abstract : Expanding the toolbox of enzymes for peptide head‐to‐tail cyclization : We successfully employed peptiligase variants such as omniligase‐1 for the efficient and scalable one‐pot cyclization/folding assembly of disulfide‐rich macrocyclic peptides, including the cyclotides MCoTI‐II and kalata B1 as well as the θ‐defensin RTD‐1. Multiple ligation sites allow a highly modular synthesis and facilitate cyclotide grafting studies.